(untitled) - Meloni, Diego Ariel; Gulotta, Marta Rosalía; Silva, Diolina Moura; Arraiza, María Paz (Universidad Nacional de Cuyo. Facultad de Ciencias Agrarias)

Effects of salt stress on germination, seedling growth, osmotic adjustment, and chlorophyll fluorescence in Prosopis alba G. (2019)

(untitled)
Fil: Meloni, Diego Ariel. Universidad Nacional de Santiago del Estero (Argentina)